Why Teach Abstractions in Primary and Secondary School? Evidence against Current Trends - Zapico, Martín Gonzalo (2019)
The argentine educational system today lives a crisis situation, which becomes evident when high school graduates must undertake a college degree: they do not have the basic skills of reading and writing, which results in a high dropout rate in their freshman year. This state of affairs can be attributed to an approach that chose to ignore the direct teaching of abstractions, postulating that they can be learned indirectly. On this basis, we propose that the direct teaching of abstractions and complex concepts is necessary to promote not only a better academic performance but a better quality of life in general. To argue this position, we will resort the opinion of teachers, experts in the field, theoretical studies and practical experience, highlighting the urgency of a return to these practices to promote the development of a critic view of reality in a world that tends increasingly leans towards disinformation and over-simplifications. In a first instance, theoretical evidence will be analyzed about the importance of abstractions; then, the linguistic evidence will be addressed and finally the experimental work will be reviewed. Evidence from the analysis suggests that a return to teaching methods where abstractions play a key role would improve the performance that students have regarding reading and writing problems.